Harvest of Superficial Layers of Fat With a Microcannula and Isolation of Adipose Tissue–Derived Stromal and Vascular Cells. (May 2014) - Trivisonno, Angelo; Di Rocco, Giuliana; Cannistra, Claudio; Finocchi, Valerio; Torres Farr, Sebastian; Monti, Massimo; Toietta, Gabriele
Background: Adipose tissue is a source of stromal and vascular cells suitable for regenerative medical applications. Cell recovery depends on several factors, including the characteristics of the cannula used to harvest tissue. Objectives: The authors assess whether aspiration of superficial layers of adipose tissue performed with a microcannula, rather than a standard cannula, allows for improved isolation of stromal and vascular cells, and they evaluate the angiogenic potential of the isolated cells in vitro and in vivo. Methods: Adipose-derived stromal and stem cells (ADSC) were collected from the lipoaspirate of the abdomen and hip regions of 6 healthy female donors. For adipose tissue harvest, several options were compared: (1) a rounded-tip cannula with a length of 170 mm, a diameter of 3 mm, and a single elliptic suction port on the side near its distal end (port diameter: 3 × 9 mm) or (2) a rounded-tip infiltration cannula with a length of 170 mm, a diameter of 2 mm, and 5 round ports placed spirally along the sides of the distal cannula shaft (each port diameter: 1 mm) (Shipper Medical Technologies Corporation, Centennial, Colorado). Isolated cells were characterized for (1) expression of the endothelial specific marker CD31 by immunohistochemical and cytofluorimetric analyses and (2) tubular-like structure formation using a 3-dimensional angiogenesis assay on Matrigel. Human ADSC were transduced to express firefly luciferase as a marker suitable for bioluminescent tracking and transplantation studies into immunosuppressed mice were performed. Results: ADSC yield was determined to be significantly higher in samples collected with the microcannula ( P = .04). Moreover, isolated cells acquired typical endothelial-like morphology in vitro, formed capillary-like structures, and expressed the distinctive endothelial cell marker CD31. Cells implanted into immunosuppressed mice persisted for several weeks in areas undergoing neovascularization. Conclusions: These results suggest that aspiration of adipose tissue with a microcannula can be a minimally invasive method to obtain clinically relevant numbers of stromal and vascular cells useful for autologous transplant procedures and for promoting tissue regeneration and neovascularization.